China in Globalization : the Insertion of the Chinese Automotive Sector in Algeria and Morocco - Pairault, Thierry (DEMO, 2017)
From Bandung to the present day, China's place and role in Africa have evolved considerably. Since the beginning of the 2000s, there has been a shift from politics to economics. China's relations with Africa are not immune to these developments, even though the latter are less advanced, as illustrated by the current low level of inclusion of African countries in the «new silk roads» strategy. The purpose of our contribution will be to show through the will of integration in the Algerian and Moroccan economies of Chinese car manufacturers and suppliers that the shift towards a dominant market logic in the Sino- African relations is also accompanied by a progressive changeover between regional poles. In addition, there will be a hijacking of China's internationalization. Partnerships signed by Chinese companies in the Algerian and Moroccan automobile sectors are less the manifestation of their integration than a modality of the globalization of traditional manufacturers through their Chinese partners. (original abstract)
Keywords: Globalization; Globalization of markets; Motorization; Motorization market; Automotive sector; Economic relations; Economic development; Economic development of the country